POLA ASUH ORANG TUA DALAM MEDIDIK ANAK MELESTARIKAN LINGKUNGAN - Yadnyawati, Ida Ayu Gde (Bumi Lestari, 2010)
Environment is a part of the child\'s life. In the environment, students live and interact in the chain of life, called ecosystems. Interdependence between biotic and abiotic environment can not be avoided. That is the law of nature that must be faced by the children as belonging to live beings part of biotic groups. During life, the child can not avoid the natural environment and socio-cultural environment. The interaction of these two different environments is always happening in filling the child\'s life. The family is the neighborhood children. Families play important roles as first and foremost educators. Habits, social attitudes, and creativity of children are affected by parents involvement. Education in this family would not be separated from environmental influences. Therefore, parenting manner is very important role in helping children for environmental preservation.